Physicochemical characteristics of Cross River and costal areas of Cross River and Akwa Ibom States, Nigeria (2006)
A study was carried out to determine the physico-chemical characteristics of the Cross River and coastal area of Cross River and Akwa Ibom state of Nigeria. Water samples were collected in dry (March and December) and wet (July and October) seasons during four cruises on parts of Cross River and Ibeno coastline of Akwa Ibom state between 1999 and 2002. Surface (0-15cm and bottom (2-13m) water were assessed at nine stations for for temperature, dissolved oxygen (D, O) hydrogen ion concentration (pH), total dissolved solids(TDS) total suspended solid (TSS), salinity, nitrite, nitrate, ammonium, phosphate, sulphate, silicate, calcium magnesium, sodium, chloride, and potassium. Spatial variations (p<0.05) were observed in the water quality parameters examined while temporal variations were generally not. Station 8(a marine station and site of major oil industry activity) was significantly different from all other stations (p<0.05) in all parameters considered. It was concluded that the water quality of the area should be monitored regularly to keep track of the water quality as all these areas were impacted by a major oil silage in 1999.